What are students' needs and preferences for academic feedback in higher education? A systematic review. (February 2020) - Paterson, Catherine; Paterson, Nathan; Jackson, William; Work, Fiona
Abstract: Objective: Feedback is a fundamental factor within the learning process for students. However, it is widely known that students generally report that feedback is done sub-optimally in higher education. Therefore, this systematic review aims to identify students' needs and preferences for academic feedback in higher education. Design, data sources, review methods . A systematic review was conducted according to the PRISMA Statement Guidelines. Electronic databases were searched using a range of keywords and the findings were integrated in a narrative synthesis. Quality appraisal was undertaken. Results: 5884 articles were retrieved, and 36 papers included. Three themes emerged across a wide range of academic disciplines which included: 1) preferences for feedback, 2) multimodality feedback and 3) emotional impact. Overall, quality feedback was related to the timeliness of feedback; balance between positive and constructive comments; direct feedback on content; linguistic clarity and legibility; grade justification and feeding forward. Conclusion: This review has informed several important implications for practice uniquely from the students' perspectives. Educators are encouraged to implement the evidence-based preferences for student feedback in their daily practice. Students value multimodality feedback which is personalised to enable students to feed forward in their own individual learning journeys. Future research should explore whether demographic variables influence student feedback needs over time. We would recommend that future studies need to employ a rigorous methodology to avoid the shortcomings in the studies already conducted in this area.